2014
DOI: 10.1111/cns.12322
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Gray Matter Heterotopia

Abstract: The objective of this article is to review the pathophysiological bases of gray matter heterotopia and to appreciate their involvement in brain cortical development and functional consequences, namely epilepsy. The development of the cerebral cortex results from complex sequential processes including cell proliferation, cell migration, cortical organization, and formation of neuronal networks. Disruption of these steps yields different types of cortical malformations including gray matter heterotopia, characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 134 publications
(150 reference statements)
0
39
0
9
Order By: Relevance
“…The histological analysis in the present study demonstrated dyslamination and heterotopic cells in the MAM and LUZ (as an MT receptor antagonist) groups. Heterotopic cells were recognized by the ectopic position of neurons (Watrin et al, 2015). Furthermore, ectopic cells, as well as dysmorphic cells with a large size and abnormal shape, were detected in these groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological analysis in the present study demonstrated dyslamination and heterotopic cells in the MAM and LUZ (as an MT receptor antagonist) groups. Heterotopic cells were recognized by the ectopic position of neurons (Watrin et al, 2015). Furthermore, ectopic cells, as well as dysmorphic cells with a large size and abnormal shape, were detected in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the histological signs of cortical malformation include dyslamination and the presence of heterotopic and dysmorphic cells (Fauser et al, 2004; Watrin et al, 2015). Our findings corroborated a previous study reporting delayed neurodevelopment and cortical malformations in the offspring of animals with melatonin deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2,3] Periventricular heterotopia -mutation in FLNA gene on Xq28 were found on 100% of families with X linked bilateral periventricular nodular heterotopia and 26% of sporadic cases with coagulopathy and cardiovascular malformation may be associated. [4] Mutation in the gene locus ARFGEF2 (20q 13.13) present with PNH with microcephaly. Mutation in gene (C6 orf 70 6q27, FAT4 (4q-28.1), DCHS1 (11p15.4) are other genes associated with PNH.…”
Section: Subcortical Heterotopiamentioning
confidence: 99%
“…Heterotopia are most commonly isolated anomalies, but may be part of number of syndromes including chromosamal anomalies and fetal exposure to toxins include alcohol. [4] Subcortical heterotopia may present with epilepsy in both men and women. The more extreme heterotopia, the greater the CNS deficit.…”
Section: Subcortical Heterotopiamentioning
confidence: 99%
“…These provide robust tools for assessing differences in, for example, the proportion of grey matter voxels between two or more groups. Reductions in grey matter volume are a commonly observed feature of normal ageing [10], and are also seen in diseases such as amyotrophic lateral sclerosis [11], epilepsy [12], Alzheimer’s disease [13] and schizophrenia [14]. However, differences in tissue structure can be subtle and difficult to identify consistently between studies [14,15].…”
Section: Introductionmentioning
confidence: 99%